The Role of Green Products and Brand Experience in the Decision to Use Grab Services in Medan City - Elisabeth Nainggolan; Sri Rezeki; Afrizal Loebis; Kelvin Lie (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the role of Green Product and Brand Experience in the decision of Grab service users in Medan City. This study uses a quantitative approach with a survey method, involving 140 respondents who use Grab services in Medan City. Data was collected through a questionnaire that measured respondents' perception of Green Product, Brand Experience, and their decision to use Grab services. Validity and reliability tests were carried out to ensure the validity of the research instruments, with results showing that all instruments were valid and reliable. The data obtained was analyzed using multiple linear regression to test the influence of independent variables (Green Product and Brand Experience) on dependent variables (User Decisions). The results of the study show that Green Product and Brand Experience have a significant influence on users' decisions to choose Grab services. Simultaneously, these two variables influence user decisions, with Green Products contributing to increased environmental awareness, while Brand Experience affects users' perception and loyalty to the Grab brand. The regression model used in this study meets classical assumptions, such as normality, the absence of multicollinearity, and the absence of heteroscedasticity, so this model can be relied upon for further analysis. Based on these findings, Grab is advised to further optimize the promotion of GrabElectric services as an environmentally friendly product and continue to improve the brand experience to attract more users, especially those who care about environmental sustainability issues. This research contributes to the understanding of how environmental factors and brand experience can influence users' decisions in choosing app-based transportation services.